2020
DOI: 10.1126/sciimmunol.aax1686
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced IL-36R signaling promotes barrier impairment and inflammation in skin and intestine

Abstract: Deficiency in interleukin-36R (IL-36R) antagonist caused by loss-of-function mutations in IL-36RN leads to DITRA (deficiency of IL-36 receptor antagonist), a rare inflammatory human disease that belongs to a subgroup of generalized pustular psoriasis (GPP). We report a functional genetic mouse model of DITRA with enhanced IL-36R signaling analogous to that observed in patients with DITRA, which provides new insight into our understanding of the IL-36 family of molecules in regulating barrier integrity across m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…In murine models of IL-23 or IL-36α injection, IL-36R antibodies inhibit inflammatory responses, with significant attenuation of skin thickening and expression of psoriasis-relevant genes [ 51 ]. Hovhannisyan and colleagues studied a mouse model with decreased affinity of IL-36Ra to IL-36R, leading to enhanced IL-36R signaling [ 52 ]. Using IL-36R monoclonal antibodies, they demonstrated that IL-36R blockade led to the down-regulation of IL-17A, IL-17F, and IL-23, as well as to reduced skin thickness and reduced IL-6, IL-1β, and TNFα cytokines in the skin [ 52 ].…”
Section: Targeting Il-36r In Psoriasismentioning
confidence: 99%
See 3 more Smart Citations
“…In murine models of IL-23 or IL-36α injection, IL-36R antibodies inhibit inflammatory responses, with significant attenuation of skin thickening and expression of psoriasis-relevant genes [ 51 ]. Hovhannisyan and colleagues studied a mouse model with decreased affinity of IL-36Ra to IL-36R, leading to enhanced IL-36R signaling [ 52 ]. Using IL-36R monoclonal antibodies, they demonstrated that IL-36R blockade led to the down-regulation of IL-17A, IL-17F, and IL-23, as well as to reduced skin thickness and reduced IL-6, IL-1β, and TNFα cytokines in the skin [ 52 ].…”
Section: Targeting Il-36r In Psoriasismentioning
confidence: 99%
“…Hovhannisyan and colleagues studied a mouse model with decreased affinity of IL-36Ra to IL-36R, leading to enhanced IL-36R signaling [ 52 ]. Using IL-36R monoclonal antibodies, they demonstrated that IL-36R blockade led to the down-regulation of IL-17A, IL-17F, and IL-23, as well as to reduced skin thickness and reduced IL-6, IL-1β, and TNFα cytokines in the skin [ 52 ]. In addition, they found comparable efficacy of anti-IL36R and anti-IL-12p40 (a murine surrogate of ustekinumab) antibodies in reducing IMQ-induced skin inflammation in vivo [ 52 ].…”
Section: Targeting Il-36r In Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…The synovial plasma cells were identified as the primary source of IL-36 expression, which in turn induced production of inflammatory cytokines by fibroblast like synoviocytes (FLS) [11]. In animal models of psoriasis, blockage of IL-36R results in disease amelioration accompanied by reduction in IL-17, leukocyte infiltration and keratinocyte activation [18][19][20]. Most importantly, IL-17 stimulates keratinocytes to produce IL-36 which in turn induce IL-17 production leading to a positive feed-back loop in psoriasis [21], possibly resulting in the dysregulated state of immune response.…”
Section: Introductionmentioning
confidence: 99%